SARS‐CoV‐2 and its relationship with the genitourinary tract: Implications for male reproductive health in the context of COVID‐19 pandemic. (30th September 2020) - Hallak, Jorge; Teixeira, Thiago A.; Bernardes, Felipe S.; Carneiro, Felipe; Duarte, Sergio A. S.; Pariz, Juliana R.; Esteves, Sandro C.; Kallas, Esper; Saldiva, Paulo H. N.
Abstract: Background: The current outbreak of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, named coronavirus disease 19 (COVID‐19), is not the first well‐known spillover of an animal originated virus to infect humans. However, one of the few to make such a fast jump in a powerful evolutionary shortcut. The incredible pattern of aggressiveness worldwide since the beginning of the outbreak is that up to 20% of those infected need hospitalization and 5% evolve to critical conditions, not limited to respiratory‐related issues, but rather to systemic involvement. Objective: This study aims to summarize the current knowledge about the effects of SARS‐CoV‐2 infection on the male genitourinary tract. Materials and methods: A narrative review was carried out to identify articles on the SARS‐CoV‐2 infection on the male genitourinary system. Results: Considerations were made about the molecular characteristics of SARS‐CoV‐2 and immune response to coronavirus. We discussed the influence of the virus on the urinary system, potential mechanisms of COVID‐19‐ related acute kidney injury (AKI), and the role of cytokine release syndrome on the renal pathophysiology of the disease. In the male reproductive tract, it was discussed the testis' vulnerability to SARS‐CoV‐2 invasion and the possible adverse effects on its function and the seminal findings of COVID‐19. Discussion and conclusion: During the COVID‐19 pandemic, an international coordinated scientific effort must arise to understand the role of the urogenital system in the SARS‐CoV‐2 infection in the clinical setting.